Identifikasi Elemen Lunak dan Elemen Keras di Objek Wisata Mahapraja, Banjar Puraja, Desa Peninjoan, Kecamatan Tembuku, Kabupaten Bangli - Wija Yuana, Dewa Ayu Anggi Wiwit; Sugianthara, Anak Agung Gede; Semarajaya, Cokorda Gede Alit (Jurnal Arsitektur Lansekap, 2024)
Identification of Soft and Hard Elements in Mahapraja Tourism Object, Banjar Puraja, Peninjoan Village, Tembuku District, Bangli Regency. Mahapraja is a tourist attraction located in Banjar Puraja, Peninjoan Village, Tembuku District, Bangli Regency. Tourism object that makes the park as the main function. The garden is designed to give the impression of being one with the surrounding countryside. Mahapraja prioritizes the natural green of the countryside, so it is more to maximize the potential of the existing nature or not change the nature much. Not only for beauty, but whether it is in accordance with the functions and activities in the area or not. So it is necessary to do this research related to the identification of soft elements and hard elements as supporting facilities for space functions and activities. The purpose of this research is to identify the suitability of soft and hard elements as supporting facilities for spatial functions and activities as well as the conditions of each of these elements. The method used is the survey method with observation techniques, interviews, and literature study. The stages are the data inventory, data analysis, and synthesis stages. Analysis and synthesis were carried out in a qualitative descriptive manner. The results of the study show that in each area there are still several facilities that do not yet support the function and activities of the space, both soft and hard elements. The condition of each element is still in good condition and suitable for use and there are those that still need improvement.